Aktantski modeli - Kralj, Lado (Primerjalna književnost, 1998)
Actantial models. - This treatise follows and comments on the historical development of actantial models. Their currently established form and terminology were established by A.J.Greimas who applies them to all literary genres: A.Ubersfeld took Greimas' idea and adjusted it to the special demands of drama, and later on made it prominent as a useful instrument of dramatic analysis. The actantial model actually appeared in its rudimentary form in thesecond half of the 18th century, when first defined by Italiam dramatist Carlo Gozzi, who presumably derives it from the special structure of charecter and action in commedia dell'arte. In later phases of development, actantial models were twice used to analyze drama (by G. Polti and É. Souriau)and only once in narrative, i.e. a folktale (by V. Propp). Greimas added a vital new dimension in this development. On the basis of the thesis oflinguist L. Tesniere, he defined the actantial modelas an extrapolation of syntactic structure, which also means that every narrative and hereafter the plot as a whole has its own subject, object, sender, receiver, helper and opponent. The present paper deals with variants of the actantial model since Gozzi, with the aid of Greimas' uniform terminology. In this way, a comparison between models becomes much clearer, if not impossible without the Greimas terminology. On the basis of these comparisons, A. Ubersfeld's work can be seen as a convergence of historical forms, while drama can be described as the most suitable for this kind of analysis. Ubersfeld also introduced special features, including the possibility that an actant is abstract, i.e. non-personal, or even that some actantial positions remain unoccupied. Such unoccupied actantial positions very clearly indicate that the most essential characteristic feature of the play discussed is constituted per negationem, i.e. by the absence of some fundamental and almost indispensable primary matter. Ubersfeld's complex, though easily discernible apparatus enables the analysis of drama which originates from a deep, archaic, as it were, structure of the text, which may be better protected from ideological projections than any other method.
Keywords: literarna teorija; literary theory; teorija drame; dramska zgradba; dramska tehnika; aktantski modeli